Intramolecular interaction of yeast TFIIB in transcription control - Zhang, Dong-Yi (Oxford University Press, 2000)
The general transcription factor TFIIB is a key component in the eukaryotic RNA polymerase II (RNAPII) transcriptional machinery. We have previously shown that a yeast TFIIB mutant (called YR1m4) with four amino acid residues in a species-specific region changed to corresponding human residues affects the expression of genes activated by different activators in vivo. We report here that YR1m4 can interact with several affected activators in vitro. In addition, YR1m4 and other mutants with amino acid alterations within the same region can interact with TATA-binding protein (TBP) and RNAPII normally. However, YR1m4 is defective in supporting activator-independent transcription in assays con-ducted both in vitro and in vivo. We further demonstrate that the interaction between the C-terminal core domain and the N-terminal region is weakened in YR1m4 and other related TFIIB mutants. These results suggest that the intramolecular interaction property of yeast TFIIB plays an important role in transcription regulation in cells.